Development of Augmented Reality-Based Learning Media on Concept of Hydrocarbon to Improve Multi-representation Ability - Vita Fitria Ningrum; Woro Sumarni; Edy Cahyono (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to design and develop learning media based on augmented reality on hydrocarbon material and its validity to determine the media's feasibility and increase students' multi-representation ability. This research is a type of development research using Design Research and Development (R&D). The product validity test phase was carried out by two material experts and three media experts. In addition, testing was carried out on the responses of the participating students. The implementation stage of learning was carried out by class X TKJ 2 SMK Gondang Pekalongan with a total of 32 students. The data analysis technique used a questionnaire instrument and the technical descriptive statistical analysis. The results of this study are: (1) the development of augmented reality-based learning media on hydrocarbon material in the form of an android application consisting of five main menus, namely basic competencies and indicators, materials, AR camera, practice questions, and the identity of the researcher, as well as seven molecular cards of the structure chemical compound molecules; (2) validity assessment by material experts with an average score of 85% in the "very valid" category and the validity assessment by media experts with an average score of 94% in the "very valid" category; (3) the feasibility test results for using media in the implementation of learning obtained an average student response score of 78%, with the "feasible" category used as learning media. The increase in multi-representation abilities is shown by increasing student learning outcomes using multi-representation questions, including macroscopic, submicroscopic, and symbolic levels. The macroscopic level increased by 27.50%, the submicroscopic increased by 36.70%, and the symbolic level increased by 33.30%. The results of this study indicate that augmented reality-based learning media on hydrocarbons is very suitable for use in chemistry learning and has been proven to increase students' multi-representation abilities